Matrices of Native and Oxidized Pectin and Ferrous Bisglycinate and Their In Vitro Behavior through Gastrointestinal Conditions - Martin Jimenez; Daniela Viteri; Daniela Oña; Marco Leon; Valeria Ochoa-Herrera; Natalia Carpintero; Francesc Sepulcre; Jose F. Alvarez-Barreto (Colloids and Interfaces, 2023)
Colloidal matrices of native and oxidized pectin were developed to improve iron bioavailability through the digestive tract. Ferrous bisglycinate (Gly-Fe), obtained by precipitation of glycine chelation to Fe2+, was mixed with native and peroxide-oxidized citrus pectin, and subsequently lyophilized. Controls included matrices with iron and glycine without chelation. The resulting samples were characterized through FTIR, SEM, and TGA/DSC before and after in vitro digestion, which was performed in simulated salivary, gastric, and intestinal fluids. During these digestions, swelling capacity and iron release were assessed. All matrix formulations were porous, and while pectin oxidation did not alter architecture, it changed their properties, increasing thermal stability, likely due to greater number of interaction possibilities through carbonyl groups generated during oxidation. This also resulted in lower swelling capacity, with greater stability observed when using the chelated complex. Higher swelling was found in gastric and intestinal fluids. Pectin oxidation also increased retention of the chelated form, contrary to what was observed with unchelated iron. Thus, there is an important effect of pectin oxidation combined with iron in the form of ferrous biglyscinate on matrix stability and iron release through the digestive tract. These matrices could potentially improve iron bioavailability, diminishing organoleptic changes in fortified iron foods.